TOBA BATAK HOUSE OF HUTA BAGASAN IN JANGGA DOLOG VILLAGE - Margareta Maria Sudarwani; Iwan Priyoga (Universitas Sebelas Maret Surakarta, 2019)
Each region basically has a traditional house that has characteristics in accordance with the local wisdom of each region. Each traditional house will reflect the identity that grows in the area. The physical structure of the building of traditional houses in anthropology in different traditional societies will bring up building elements that are depicted in the form of ornaments as a symbol of meaning that has special meaning in the area. Symbolizing the building of a traditional society, the building elements have a special meaning that is recognized by the builders as an important element for building strength and stability. Research into the homes of a traditional society gives us some valuable views for the conception of housing. Likewise in the case study of a traditional house in Jangga Dolok Village, Lumbun Julu District, Toba Samosir Regency, North Sumatra Province. Majority of the people are Batak people. Batak Traditional Houses have a major influence in the spatial planning of the area. Besides that, the symbolization of houses living in Batak people cannot be separated from the influence of socio-cultural life and all aspects manifested in the symbolization of Batak Traditional Houses which have special meaning.